"Even our Dairy Queen shut down": Risk and resilience in bioenergy development in forest‐dependent communities in the US South. Issue 2 (June 2017) - Hitchner, Sarah; Schelhas, John; Brosius, J. Peter
Abstract: Wood‐based bioenergy in the US South is a key element in a sociotechnical imaginary that brings together rural development, energy independence, and environmental sustainability; it is also a key element in another imaginary in which powerful interest groups from the private sector and government collude in ways that enrich them regardless of success of the endeavor, while simultaneously posing risks to the host community. We contend that bioenergy development can introduce new risks for local communities that are often overlooked in imaginaries promulgating bioenergy as a driver of community resilience. Based on ethnographic research in Soperton, Georgia, site of the failed Range Fuels cellulosic ethanol plant and current LanzaTech experimental plant, we show how various aspects of these imaginaries merge, overlap, and compete as different actors experience the opening—and sometimes closure—of these facilities in rural communities that are often economically depressed, politically conservative, and deeply rooted in forestry both economically and culturally.